2021
DOI: 10.3390/nu13103568
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Major Adverse Cardiovascular Events (MACE) after Bariatric Surgery in Patients with Obesity and Cardiovascular Diseases: A Systematic Review and Meta-Analysis

Abstract: Cardiovascular diseases (CVDs) are the leading cause of death worldwide and obesity is a major risk factor that increases the morbidity and mortality of CVDs. Lifestyle modifications (e.g., diet control, physical exercise and behavioral changes) have been the first-line managements of obesity for decades. Nonetheless, when such interventions fail, pharmacotherapies and bariatric surgery are considered. Interestingly, a sudden weight loss (e.g., due to bariatric surgery) could also increase mortality. Thus, it … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 53 publications
0
19
1
Order By: Relevance
“…It also reduces the risk of cardiovascular diseases such as myocardial infarction and ischemic stroke and decreases overall mortality [75][76][77]. A meta-analysis conducted by Sutanto et al showed significant reduction in the incidence of major adverse cardiovascular events in bariatric surgery group as compared to the no-surgery group (OR = 0.49; 95% CI 0.40-0.60; p < 0.00001; I2 = 93%) [78]. Among recently available surgical methods, Roux-en-Y gastric bypass (RYGB) and laparoscopic sleeve gastrectomy (LSG) are the most commonly performed worldwide.…”
Section: Bariatric Surgery and Nafldmentioning
confidence: 99%
“…It also reduces the risk of cardiovascular diseases such as myocardial infarction and ischemic stroke and decreases overall mortality [75][76][77]. A meta-analysis conducted by Sutanto et al showed significant reduction in the incidence of major adverse cardiovascular events in bariatric surgery group as compared to the no-surgery group (OR = 0.49; 95% CI 0.40-0.60; p < 0.00001; I2 = 93%) [78]. Among recently available surgical methods, Roux-en-Y gastric bypass (RYGB) and laparoscopic sleeve gastrectomy (LSG) are the most commonly performed worldwide.…”
Section: Bariatric Surgery and Nafldmentioning
confidence: 99%
“…With the advent of laparoscopy, as for other digestive procedures [ 3 , 4 ], bariatric surgery is increasingly used to induce weight loss and remission of obesity-related metabolic complications and it has been demonstrated to be more effective and cost-effective than behavioral/medical therapy [ 5 ]. Furthermore, bariatric surgery has led to a reduction in the mortality rate of morbid obese patients, especially after major adverse cardiovascular events [ 6 ]. At present, the most established bariatric procedures include sleeve gastrectomy and Roux-en-Y gastric bypass (RYGB) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The usage of bariatric surgery in the severe obesity treatment has a number of advantages, including maintainable weight loss, improvement or elimination of some metabolic diseases, and improving life expectancy [ 7 ]. A recent systematic review and meta-analysis on ten studies reported that bariatric surgery reduces the incidence of Major Adverse Cardiovascular Events (MACE) in patients with obesity and cardiovascular diseases [ 8 ]. The combination of these advantages with the sustained decrease in complications has led to significant growth in appeal for bariatric surgery worldwide [ 9 ].…”
Section: Introductionmentioning
confidence: 99%